Práticas pedagógicas e o uso de tecnologias digitais no ensino remoto: narrativas de professores do ensino médio de escolas em Coari/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The object of this research is pedagogical practices and the use of digital technologies in remote education, in which data was collected through narrative interviews with secondary school teachers. With the firm purpose of unraveling the concern that drove this research, the following problem emerged. What are the perceptions of philosophy and sociology teachers in relation to the use of DICTs in teaching practices in the context of remote teaching, which has been instituted as a result of COVID-19? Followed by the general objective of understanding the perceptions of Philosophy and Sociology teachers in relation to the use of DICTs in pedagogical practices in the context of emergency remote teaching in state schools in Coari/AM. The research was based on a qualitative approach, in which the data was collected through narrative interviews, which were recorded, transcribed and then analyzed through the lens of Content Analysis. The corpus analyzed revealed the role of teachers in adopting important methodological initiatives to make teaching meaningful, in the face of the challenging scenario of the pandemic. Among the findings of this research, we highlight the comings and goings of the subjects Philosophy and Sociology in the public school curriculum, which need public policies that value them. There are also concerns about the region's geographical challenges, which compromise internet access. The results indicate that persistent and emerging situations create obstacles to the effective use of technologies in the practice of teachers. Therefore, it is necessary to overcome the lack of technological resources in schools, as well as the lack of preparation of teachers in relation to the use of these resources, in addition to the lack of equity in student access and school infrastructure, as well as providing opportunities for debates on the implementation of public policies in public school education. In light of the above, the research leads to reflections on the use of ICTs in schools as not being an end in itself, but rather a means to achieve greater educational goals. It is therefore important for public authorities to ensure that technological innovation reaches educational institutions, but it is also necessary to provide conditions for inclusion and use by all those who are part of the school.
Keywords: CIENCIAS HUMANAS: EDUCACAO; Práticas pedagógicas; Ensino médio; Tecnologias digitais; Filosofia e Sociologia